Stem Cell Therapy For Men’s Vitality: A Comprehensive Review And Meta-Analysis - Deby Susanti Vinski; Jaime Rodriguez Quintosa; Svetlana Trofimova; Andi Kurniawan Nugroho; Natasha Cinta Vinski; Marhaen Hardjo (Riviera Publishing, 2024)
One of the many potential benefits of stem cell therapy is that it may enhance men’s vitality by addressing conditions such as erectile dysfunction and hypogonadism. The current comprehensive review and meta-analysis evaluate the efficacy, safety, and mechanisms of stem cell therapy in improving male sexual health. Data from previously published clinical trials, reviews, and preclinical studies indicate that stem cell therapy significantly enhances erectile function, increases testosterone levels, and improves sperm quality. The regenerative potential of mesenchymal stem cells (MSCs), including their ability to differentiate into various cell types and secrete bioactive molecules, underpins these benefits. Additionally, MSCs modulate the immune response, reducing inflammation and promoting tissue repair. Despite these promising results, current research is limited by heterogeneity among studies, lack of long-term data, and the absence of standardized treatment protocols. Future research can focus on large-scale randomized controlled trials with standardized protocols to validate the long-term efficacy and safety of stem cell therapy. The results of the review support the potential of stem cell therapy as a novel approach in regenerative medicine, offering innovative solutions for men’s health and vitality. Addressing the current limitations and exploring future directions will pave the way for the clinical adoption of stem cell therapy, advancing the treatment options for conditions affecting men’s vitality and improving the quality of life for millions of men worldwide.